1991
DOI: 10.2337/diab.40.6.748
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DQA1 and -DQB1 Alleles Associated With Genetic Susceptibility to IDDM in a Black Population

Abstract: Transracial analysis provides a method of distinguishing primary associations between insulin-dependent diabetes mellitus (IDDM) and HLA class II alleles from those secondary to linkage disequilibrium. Blacks show DR-DQ relationships that are different from other races and are a useful group in which to investigate HLA-D region associations with IDDM. In this study, the frequencies of HLA-DQA1 and -DQB1 alleles in Afro-Caribbean IDDM and control subjects were compared. Alleles were identified with sequence-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 0 publications
2
24
1
Order By: Relevance
“…The results were similar to those of our previous study of a UK-based Jamaican population, demonstrating that differences in environment do not alter the genetic requirements for disease development. Subtyping at the DRB1 locus has revealed heterogeneity between associations with type 1 Significant in UK-based study of 37 D and 82 C only (Mijovic et al , 1991); NS in the present study.…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…The results were similar to those of our previous study of a UK-based Jamaican population, demonstrating that differences in environment do not alter the genetic requirements for disease development. Subtyping at the DRB1 locus has revealed heterogeneity between associations with type 1 Significant in UK-based study of 37 D and 82 C only (Mijovic et al , 1991); NS in the present study.…”
Section: Discussioncontrasting
confidence: 47%
“…In our previous UK-based study (Mijovic et al , 1991), DRB1*07 and DRB1*11 haplotypes carrying DQA1*0301/DQB1*02 were positively associated with diabetes. In contrast, in the present study neither haplotype showed any significant association with disease ( Table 3).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In disease association studies, an allele is considered negatively associated, or protective, when there is a significantly lower frequency of the allele in the patient population compared with the controls. This has been observed for the DQB1*0602 allele and IDDM in numerous studies and in most races [10,11,[19][20][21][22][23][24][25][26]. In many of these studies some patients have been identified as having the protective allele, as occurred when we originally studied 266 IDDM patients [10].…”
Section: Discussionmentioning
confidence: 59%
“…The latter shows significant abnormalities, including basement membrane thickening, which is the histological hallmark of diabetes microangiopathy. demonstrating the primacy of the HLA D region in susceptibility to Type 1 diabetes [26][27][28][29][30][31][32] and later suggesting that specifically the HLA DQA1 and HLA DQB1 alleles were the primary susceptibility determinants [33][34][35][36][37][38][39][40][41][42][43][44]. A successful collaboration with John Todd (now Professor of Human Genetics in Cambridge) led to an important paper in Nature in 1989 [39].…”
Section: And So To Geneticsmentioning
confidence: 99%